Pengaruh Harga Tiket dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Kereta Api Argo Parahyangan Rute Bekasi-Bandung - Indah Sari, Afri Neta; Endriastuti, Yenia (STIE AMKOP, 2024)
This study aims to analyze the effect of ticket prices and service quality on purchasing decisions on the Argo Parahyangan Train. The population in this study were consumers who had traveled using the Argo Parahyangan Train. The sample in this study was 100 respondents. The sampling technique used was Convenience Sampling. Data collection was carried out using a questionnaire measured with a Likert scale. The data analysis technique used was multiple linear regression. The results of this study indicate that ticket prices have a positive and significant effect on purchasing decisions on the Argo Parahyangan Train. Service quality has a positive and significant effect on purchasing decisions on the Argo Parahyangan Train. Ticket prices and service quality together affect purchasing decisions on the Argo Parahyangan Train.